2018
DOI: 10.1177/0300060518798252
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of fasting blood glucose for serious coronary atherosclerosis in non-diabetic patients

Abstract: Objective To determine if high fasting blood glucose (FBG) level is an independent predictor of serious coronary lesions in patients with coronary artery disease (CAD). Methods We enrolled 64 patients who had symptoms of chest discomfort and who underwent coronary angiography. FBG was determined from blood samples and the extent of coronary artery lesions was analyzed according to Gensini score. We examined the relationships among diabetes, FBG, and coronary artery severity. Results Diabetes and FBG were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The results of asp rosin were consistent with Mirada [22] who reported significant changes in the concentration of asp rosin in patients with atherosclerosis when compared to the results of healthy individuals, since cardiac events occur as a result of free radicals and processes involving an inflammatory response, the beneficial effects of asp rosin in turn crush free radicals and reduce apoptosis [23]. Cumulative diabetes results are consistent with Hernandez [24] finding that HbA1c is a predictor of individuals at risk as well high blood hemoglobin is a predictor of cardiovascular disease regardless of fasting glucose levels, high glucose is not only a symptom of diabetes but also of stress in which these people have what is called the Stress hyperglycemia common for patients with arterial disease these findings are consistent with Zhao [25] and Shah [26] with high sugar concentration in atherosclerosis patients. In the case of insulin hormone this finding is consistent with Monnier [27] finding that there were significant differences in insulin concentration his elevation was linked to arterial sclerosis for the average person the concentration of insulin in the portal vein was much higher than in the systemic circulation.…”
Section: Discussionsupporting
confidence: 66%
“…The results of asp rosin were consistent with Mirada [22] who reported significant changes in the concentration of asp rosin in patients with atherosclerosis when compared to the results of healthy individuals, since cardiac events occur as a result of free radicals and processes involving an inflammatory response, the beneficial effects of asp rosin in turn crush free radicals and reduce apoptosis [23]. Cumulative diabetes results are consistent with Hernandez [24] finding that HbA1c is a predictor of individuals at risk as well high blood hemoglobin is a predictor of cardiovascular disease regardless of fasting glucose levels, high glucose is not only a symptom of diabetes but also of stress in which these people have what is called the Stress hyperglycemia common for patients with arterial disease these findings are consistent with Zhao [25] and Shah [26] with high sugar concentration in atherosclerosis patients. In the case of insulin hormone this finding is consistent with Monnier [27] finding that there were significant differences in insulin concentration his elevation was linked to arterial sclerosis for the average person the concentration of insulin in the portal vein was much higher than in the systemic circulation.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, a study by Iijima R, et al demonstrated that Patients with diabetes often accelerate atherosclerotic thrombosis, resulting in early, widespread, and rapidly progressing coronary artery disease ( 18 ). Tong Zhao et al concluded that hyperglycaemia was an independent predictor of severe coronary artery disease in non-diabetic patients ( 19 ). Our study definitively confirms that the association of glycemia with multi-vessel lesions is more significant in non-diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…There are relevant studies that show hypoglycemia and hyperglycemia on admission are associated with higher in-hospital mortality, The relationship between fasting blood glucose (FBG), admitted blood glucose and mean hospitalized blood glucose and in-hospital mortality was U-shaped or J-shaped [14,[16][17][18]. Park et al found a J-shaped relationship between fasting glucose levels and the risk of atherosclerotic cardiovascular disease [19].Yuhan Qin et al reviewed 958 consecutive AMI patients undergoing emergency coronary angiography, and found that FBG was positively correlated with Gensini score (r = 0.171,P&lt; 0.001) [10].Tong Zhao et al reviewed 64 patients with chest discomfort accompanied by coronary angiography; In patients with diabetes (r = 0.312,P<0.012) and non-diabetic patients (r = 0.387, P<0.010), FBG was positively correlated with Gensini score [11].Jingjing Jiang et al included 1852 patients with coronary angiography for analysis, and the result showed that FBG was positively correlated with Gensini score (r = 0.09,P<0.01), regression analysis showed that FBG was independently correlated with Gensini score [12].In 85 patients with acute coronary syndrome who underwent emergency coronary angiography and implanted stents when necessary, FPG was positively correlated with Gensini score (r = 0.568,P<0.000) [8].In 906 patients who underwent coronary angiography and had no history of diabetes, a signi cant positive correlation was found between FPG and Gensini score (r = 0.172; P = 0.011) [13].Previous studies used single truncation method to distinguish high-risk hyperglycemia [14], Only considering the effect of blood glucose on gensini score,but both hypoglycemia and hyperglycemia are high-risk factors for AMI. In our study, we used three fasting glucose thresholds, hypoglycemic group 5.30mmol/L (2.69-6.15), medium glycemic group 7.11mmol/L (6.…”
Section: Discussionmentioning
confidence: 99%
“…gensini score is mainly an evaluation index re ecting the severity of coronary artery lesions. The increase of FBG is correlated with Gensini score [8,9].Previous studies have shown a signi cant positive correlation between fasting glucose and gensini scores, con rming even in the non-diabetic range [10][11][12][13].It has been found in the past that there is a positive linear correlation between blood glucose and GENSINI score. Only the in uence of blood glucose on GENSINI is considered, without considering the in uence of other factors such as uric acid, creatinine and age on GENSINI.Previous meta-analyses and the original article used a single truncation to distinguish high-risk hyperglycemia [14], however,both hypoglycemia and hyperglycemia are high-risk factors for AMI.…”
Section: Introductionmentioning
confidence: 97%